THE SPATIAL INTERACTION OF BANDUNG CITIZENS - Lili Somantri (Indonesian Journal of Geography, 2013)
Bandung is one of the cities in Indonesia which has rapid population growth. Bandung also has high citizenmobility that comes from both other areas around the city and inside the city itself. This mobility is causeddaily activities of the citizen, eitherby studying or working. The objectives of this research are to analyze: 1) thecitizen mobility in Bandung, 2) the spatial distribution of land uses in Bandung, and 3) the spatial interaction ofBandung citizens, on the basis of land use and citizen mobility in Bandung. This research uses descriptiveanalytical method. The data is collected by using interview based technique. The collected data consist ofmobility location, type of occupation, modes of transportation, destination location, and land use type. The dataare analyzed using percentage and origin-destination matrix. The result of this research indicates that thepurpose of the citizen mobility in Bandung is mostly conducted to work by using his/her own vehicle. Most ofthe mobility is occurred around each developmental area. Furthermore, it is also revealed that there is amassive movement to Cibeunying region,n which is used for educational purposes, offices, and trading areas.